The Whitaker Test - Johnston, Richard B.; Porter, Christopher (Urology Journal, 2014)
Purpose: The Whitaker test was conceived and developed by Roger H. Whitaker (May 25, 1939) while he was a resident at Cambridge University in the late 1960s and early 1970s. The test combines a urodynamic study with antegrade pyelography to measure the pressure differential between the renal pelvis and the bladder. The test can differentiate between patients with residual or recurrent obstruction and those with dilatation secondary to permanent changes in the musculature. Materials and Methods: We present the history of the Whitaker test and its place in modern practice. Results: It is useful in evaluating patients with questionable ureteropelvic or ureterovesical junction obstruction and primary defects in the ureteral musculature. It can also be used to determine when percutaneous nephrostomy tubes can be safely discontinued in postoperative patients. Conclusion: The merit of the Whitaker test in comparison to other less invasive tests, specifically diuretic renography, is the subject of much debate. However, such debate erroneously presupposes that the tests are directly comparable, which they are not. The correct use for the Whitaker test is to assesses potential upper tract obstruction in equivocal cases and should only be utilized when equivocal results are obtained by other less invasive tests, obstruction is suspected in a poorly functioning kidney, a negative renogram with colic, intermittent obstruction, and percutaneous access already exists and the cause of dilatation needs investigating.